2011
DOI: 10.1002/prot.23009
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the intrinsic conformational preferences of noncoded α‐amino acids modified at the peptide bond into the noncoded amino acids database

Abstract: Recently, we reported a database (NCAD, Non-Coded Amino acids Database; http://recerca.upc.edu/imem/index.htm) that was built to compile information about the intrinsic conformational preferences of non-proteinogenic residues determined by quantum mechanical calculations, as well as bibliographic information about their synthesis, physical and spectroscopic characterization, the experimentally-established conformational propensities, and applications (J. Phys. Chem. B 2010, 114, 7413). The database initially c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…Introduction of N-methyl groups causes significant consequences on peptide conformation, due in part to creation of a tertiary amide which loses a potential NH hydrogen-bond donor and may adopt energetically similar cis and trans isomers [47]. Computational analysis of the N'-methyl amides of N-acetyl-N-methyland N-acetyl-alanine indicated that repulsive interactions between the N-methyl and carbonyl oxygen moieties of the former abolished the low-energy minimum β-conformer adopted by the latter [48]. In cyclic peptides, N-methyl residues have also induced backbone f and ψ dihedral angles consistent with βand γ-turn conformers [49], as well as altered side chain χ geometry [50].…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of N-methyl groups causes significant consequences on peptide conformation, due in part to creation of a tertiary amide which loses a potential NH hydrogen-bond donor and may adopt energetically similar cis and trans isomers [47]. Computational analysis of the N'-methyl amides of N-acetyl-N-methyland N-acetyl-alanine indicated that repulsive interactions between the N-methyl and carbonyl oxygen moieties of the former abolished the low-energy minimum β-conformer adopted by the latter [48]. In cyclic peptides, N-methyl residues have also induced backbone f and ψ dihedral angles consistent with βand γ-turn conformers [49], as well as altered side chain χ geometry [50].…”
Section: Discussionmentioning
confidence: 99%
“…The L. infantum (MHOM/MA/67/ITMAP-263) wild-type strain (WT), as well as the resistant mutants Sb2000.1, AmB1000.1, and MF200.5 [ 29 , 30 , 31 , 32 , 33 ], which are respectively resistant to antimony (Sb III ), amphotericin B (AmB), and miltefosine (MF), were grown in M199 medium at 25 °C supplemented with 10% fetal bovine serum, 5 μg/mL of haemin at pH 7.0, 2000 μM Sb (Potassium antimonyl tartrate trihydrate, Sigma-Aldrich, Saint Louis, MO, USA), 200 μM of MF (Miltefosine, Cayman Chem, Ann Arbor, MI, USA) or 1 μM AmB (Amphotericin B solution, Sigma-Aldrich, Saint Louis, MO, USA). Leishmanicidal values were determined in Leishmania promastigotes by monitoring the replication of parasites after 72 h of incubation at 25 °C in the presence of increasing concentrations of the different compounds by measuring A 600 using a Cytation 5 machine (BioTek-Agilent, Santa Clara, CA 9, USA).…”
Section: Methodsmentioning
confidence: 99%
“…One of the major issues in peptide drug development is the recognition by proteases and peptidases, which can be attenuated by changing the backbone through incorporation of amide bond mimics, D-isomers, β-amino acids, alteration of the termini or tetra-substituted amino acids 1,4,17,19,[31][32][33][34][35][36] . These mimics also tend to increase bioavailability, another issue which often plagues peptide drugs 17 as well as restrict conformation and therefore reduce flexibility 1,37,38 . Similar effects can also be caused by N-alkylations 1,17 , incorporation of aminoisobutyric acid 39 , other constraining amino acids 31,40,41 or by cyclisation 1,19,36,38 .…”
Section: Introductionmentioning
confidence: 99%